2008
DOI: 10.1128/aac.01211-07
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the In Vitro Efficacies of Moxifloxacin and Amoxicillin against Listeria monocytogenes

Abstract: Listeria monocytogenes is a facultative intracellular bacterium that causes severe infections associated with a high mortality rate. Moxifloxacin presents extended activity against gram-positive bacteria and has recently been suggested to be a potential alternative in the treatment of listeriosis. We evaluated the in vitro efficacy of moxifloxacin against L. monocytogenes using a combination of epidemiological and experimental approaches. The median MIC of moxifloxacin for a large collection of L. monocytogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 36 publications
0
22
0
3
Order By: Relevance
“…TKC therefore evolved as a suitable tool to evaluate antimicrobial growth inhibition of bacteria at different intracellular developmental stages (15,31). In this study, we investigated the impact of low oxygen, which can be observed in the female urogenital tract under physiological conditions, on the antichlamydial activities of doxycycline, azithromycin, rifampin, and moxifloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…TKC therefore evolved as a suitable tool to evaluate antimicrobial growth inhibition of bacteria at different intracellular developmental stages (15,31). In this study, we investigated the impact of low oxygen, which can be observed in the female urogenital tract under physiological conditions, on the antichlamydial activities of doxycycline, azithromycin, rifampin, and moxifloxacin.…”
Section: Discussionmentioning
confidence: 99%
“…However, moxifloxacin is the only one of these antibiotics released on the market and still commercially available that combines useful pharmacokinetic and pharmacodynamic properties with rapid bactericidal activity in vitro against both extracellular forms of L. monocytogenes and intracellular reservoirs of bacteria (6,14,28,36). Determination of MICs for a large collection of strains did not detect any resistant strains, whatever their origins (14). Moreover, no cross-resistance was observed with ciprofloxacin resistance expressed by clinical isolates due to an efflux mechanism (12,14).…”
Section: Listeriosis Is a Rare But Life-threatening Infectionmentioning
confidence: 99%
“…Moxifloxacin, clinafloxacin, and gemifloxacin are the most effective against intracellular L. monocytogenes (28,36). However, moxifloxacin is the only one of these antibiotics released on the market and still commercially available that combines useful pharmacokinetic and pharmacodynamic properties with rapid bactericidal activity in vitro against both extracellular forms of L. monocytogenes and intracellular reservoirs of bacteria (6,14,28,36). Determination of MICs for a large collection of strains did not detect any resistant strains, whatever their origins (14).…”
Section: Listeriosis Is a Rare But Life-threatening Infectionmentioning
confidence: 99%
“…It is significant that Maciag and co-workers recently performed Phase I trials in human subjects with can improve efficacy, being commercially available and highly effective against intracellular and extracellular listeria. 8 We are currently investigating whether more effective elimination of the vector occurs when similar experiments are conducted in immunocompetent mice.…”
Section: The Balance Between Safety and Efficacymentioning
confidence: 99%